Thoughts on infoethics - Angyal, Ádám (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2024)
This essay analyses one of the significant issues of the knowledge-based society, the ethical problems of data management in IT systems. The data management regulations are also the ethical codes of IT. Internet networks are the determining channels of communication, which raise new ethical questions. The author shows the ethical tensions and challenges that society’s IT institutional system is burdened with. He pays special attention to IT-supported phenomena of management (administration), which he compares with bureaucracy.